On numerical simulation of electromagnetic field eﬀects in the combustion process - Kalis, Harijs; Marinaki, Maksims; Strautins, Uldis; Zake, Maija (Mathematical Modelling and Analysis, 2018)
This paper deals with a simpliﬁed model taking into account the interplay of compressible, laminar, axisymmetric ﬂow and the electrodynamical eﬀects due to Lorentz force’s action on the combustion process in a cylindrical pipe. The combustion process with Arrhenius kinetics is modelled by a single step exothermic chemical reaction of fuel and oxidant. We analyze non-stationary PDEs with 6 unknown functions: the 3 components of velocity, density, concentration of fuel and temperature. For pressure the ideal gas law is used. For the inviscid ﬂow approximation ADI method is used. Some numerical results are presented.